Management of classroom acoustics by teachers at two special needs schools in Johannesburg, South Africa - Ben Sebothoma; Victor de Andrade; Nabeelah Galvaan (South African Journal of Education)
In South Africa, education is considered a basic right and our constitution calls for accessible educational contexts which ought to be conducive for learning. Even though schools are meant to be places in which learning can occur, poor classroom acoustics may threaten that basic right to education. The aim of this study was, therefore, to explore and understand how teachers in special needs schools managed classroom acoustics in their efforts to enhance learning. We report on a qualitative study using semi-structured face-to-face interviews with teachers from 2 special needs schools in Johannesburg in the Gauteng province of South Africa. A non-probability purposive sampling strategy was used to recruit participants. The results of this study confirm that classrooms in special needs schools may not be acoustically sound spaces which teachers feel may compromise effective learning. As a result, teachers reported using a variety of active and passive strategies to manage classroom acoustics in order to enhance learning. The results of this study contribute to existing knowledge on the importance of the strategies used by teachers in managing classroom acoustics. Further research is required to determine the efficacy of these and other strategies used by teachers in special needs schools.